Seismic performance of braced frame with double round steel tube. (June 2022) - Zheng, Liang; Dou, Shengrun; Wang, Wen; Ge, Hongwei; Gao, Ying; Han, Yunshan
Abstract: The new braced frame with double round steel tube was proposed in this study. To understand the seismic performance of the structure, the numerical model was established and analyzed by ABAQUS. The bearing capacity, initial stiffness, secant stiffness under the monotonic loading and the hysteresis curve, the failure process and form, the degradation of bearing capacity, the energy dissipation capacity, the fracture behaviour of the braced frame with double round steel tube under the cyclic loading of were analyzed. The analysis revealed that the height, thickness and spacing of stiffener rib had a considerable influence on the bearing capacity, initial stiffness and secant stiffness of the braced frame with double round steel tube under the monotonic loading. The hysteresis curve was full without the phenomenon of shrinkage, and the braced frame with double round steel tube had good seismic performance under cyclic loading. The height, thickness and spacing of stiffener rib had a considerable impact on the hysteresis curve, the degradation of bearing capacity, the energy dissipation coefficient and the fracture behaviour. The thickness of inner and outer-round steel tubes had little effect on hysteresis curve, the degradation of bearing capacity, the energy dissipation coefficient and the fracture behaviour. Highlights: Seismic performance of braced frame with double round steel tube was studied. The initial stiffness, linear stiffness, and bearing capacity of the structures under monotonic load were studied. Energy dissipation capacity, degradation property, failure, and deformation modes under low-cyclic loading were studied.